The Effect of annealing temperature on corrosion resistance and microstructure of Zr-Sn-Nb-Fe alloy - Zhao, G; Tiba, Zsolt; Menyhárt, József (International Journal of Engineering and Management Sciences, 2019)
The Ti-2Al-2.5Zr titanium alloy plate in beta phase water quench at different times of the reentry after annealing is implemented while primary phase number and size distribution of samples are obtained. This research is carried out on corrosion behavior in 3.5% [mass fraction] NaCl solution. Experimental study showed that after the beta phase water quenching Ti-2Al-2.5Zr titanium alloyed after 500 oC annealing when partial recrystallization happened. There seems to be lots of tiny dispersion in the alloy that was annealed with its samples of six-party [HCP] structure of Ti, Zr, Al phase 2 with the dimension below 100 nm. Reaching 500 oC when the rate of annealing at a primary phase of the sample at 550 oC is low 90% of the primary phase is less than 100 nm. The changing of the rule of present decreasing also triggers little difference overall. Precipitation in the process of annealing Zr [Nb,Fe,Cr] 2is less that proves to be good for corrosion resistance.